SCRAs with a “Brand” New Look: In Vitro Cannabinoid Activity Profiling of Generic Ban-Evading Brominated Synthetic Cannabinoid Receptor Agonists and their Analogs - M.H. Deventer; M. Persson; C. Norman; H. Liu; M. Connolly; N.N. Daeid; C. McKenzie; H. Green; C.P. Stove (Emerging Trends in Drugs, Addictions, and Health)
Introduction: Since the enactment of the Chinese generic ban (2021), the synthetic cannabinoid receptor agonist (SCRA) market has vastly changed and now encompasses unexpected, ban-evading structures such as brominated and tail-less compounds. Methods: Six new SCRAs were functionally characterized at CB1 and CB2 using 2 distinct activity-based assays, monitoring βarr2 recruitment (NanoBiT® assay) and Ca2+ mobilization (AequoScreen® assay). Results: Brominated, tailed SCRAs (ADB-5’Br-BUTINACA, MDMB-5’Br-BUTINACA) showed high efficacy and potency at CB1. Interestingly, switching the bromine for a fluorine (ADB-5’F-BUTINACA) resulted in an even more pronounced CB activity. Tail-less, brominated compounds (ADB-5’Br-INACA, MDMB-5’Br-INACA) retained activity at both receptors, albeit with decreased potency compared to their tailed counterparts, which was confirmed in both assays. Removing the bromine group from the tail-less core resulted in decreased activity (ADB-INACA), evidencing the positive effect of bromine substitution. Conclusions: This study provides essential information for both drug law enforcement agencies and health care workers, as it can be expected that the ever-lasting cat-and-mouse game that describes the SCRA market will carry on, with the surge of new and unexpected substances remaining a great challenge for several fields.